Disturbances in the form and content of utterances in dialogue and schizophatic narrative. Therapeutic implications - Lipski, Wojciech (Logopedia Silesiana, 2022)
Language disorders in schizophrenia are a natural occurance in the classifications of language disorders. However, there are still no standards of speech therapy that provide efficient therapeutic procedure. In the presented article, the author referred to schizophasia interpreted as a disorder of the content and form of expression. Both these phenomena should be the subject of speech therapy for schizophatic people. A speech therapist may be a fully fledged member of the therapeutic team together with a psychiatrist, psychologist, psychotherapist, occupational therapy specialist, and other medical staff.